2010
DOI: 10.1007/s00338-010-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic records of bleaching and endolithic algae blooms in the skeleton of the boulder forming coral Montastraea faveolata

Abstract: Within boulder forming corals, fixation of dissolved inorganic carbon is performed by symbiotic dinoflagellates within the coral tissue and, to a lesser extent, endolithic algae within the coral skeleton. Endolithic algae produce distinctive green bands in the coral skeleton, and their origin may be related to periods of coral bleaching due to complete loss of dinoflagellate symbionts or ''paling'' in which symbiont populations are patchily reduced in coral tissue. Stable carbon isotopes were analyzed in coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Hartmann et al . () suggested that some endolithic algae can substitute coral symbionts (zooxanthellae) and promote enhanced biological activity (via photosynthesis), causing, among other changes, an alteration of the δ 13 C signal of the coral skeleton in direction to more negative values. This suggestion would be compatible with the observed enhanced variation of δ 13 C across the algae‐infected portion of the coral profile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hartmann et al . () suggested that some endolithic algae can substitute coral symbionts (zooxanthellae) and promote enhanced biological activity (via photosynthesis), causing, among other changes, an alteration of the δ 13 C signal of the coral skeleton in direction to more negative values. This suggestion would be compatible with the observed enhanced variation of δ 13 C across the algae‐infected portion of the coral profile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During photosynthesis, zooxanthellae preferentially utilize forms of DIC that contain the light carbon isotope 12 C over the heavier carbon isotope 13 C. This carbon absorption model of zooxanthellae is called metabolic fractionation (Mcconnaughey, ; Swart, ). Therefore, changes in the photosynthetic intensity of symbiotic zooxanthellae could affect the isotopic composition of skeletal carbon (Hartmann et al, ). Photosynthetic intensity of symbiotic zooxanthellae is primarily controlled by irradiance and SST (Fairbanks & Dodge, ).…”
Section: Discussionmentioning
confidence: 99%
“…1). However, bleached corals do not always show this expected trend (i.e., a decrease in d 13 C s ) (Leder et al, 1991;Rodrigues and Grottoli, 2006;Hartmann et al, 2010;Levas, 2012), which is potentially due to strong kinetic effects masking changes in metabolism. The application of a data correction to remove kinetic isotope effects (Heikoop et al, 2000) might therefore reveal the masked metabolic isotope effects, and thus improve accuracy and interpretation of skeletal isotopes in bleached corals.…”
Section: Introductionmentioning
confidence: 86%